THE HISTORY OF ISLAM AND ITS DISSEMINATION IN AMBON-LEASE, MALUKU (JOURNAL OF INDONESIAN ISLAM, 2011)
Research on the history of Islam and its dissemination on the island of Maluku have hitherto been lacking analytical depth. This paper tries to fill that gap by analysisng four stages in the development of Islam on the Island, referring to approaches to study Islam and Muslims. First, the stage of integration in which Islam tried to incorporate local values and their ramifications. Second, the stage of war and resistance in which the attempts of Islam to become the dominant power on the region face a strong confrontation from the existing power. Third, the stage of reformation and renewal in which Islam interrogates and evaluates itself so as to present itself within the context of Maluku. Fourth, the stage of modern era in which Islam faces challenges not only from other religions mainly Christianity which is equally strong on the island, but also from modernity and its narratives.